(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In this article, we discuss new technologies, method development, interdisciplinary collaboration and the impact of global trends on the practice of terminological translation. By exploring these future trends and developments, this article aims to provide an overview of the evolving nature of terminological translation and its implications for language professionals, researchers and stakeholders in various fields